Involving Children in Health Literacy Research - Catherine L. Jenkins; Jane Wills; Susie Sykes (MDPI AG, 2022)
Despite the volume and breadth of health literacy research related to children, children's involvement in that research is rare. Research with children is challenging, but the principles of involvement and engagement underpin all health promotion work, including health literacy. This commentary reflects on the process of setting up a Children's Advisory Group to consult on an institutional ethnography study of health literacy work from children's standpoint. The Children's Advisory Group contributed feedback on the study ethics and design and piloted methods for rapport-building and data collection, including livestreamed draw-and-describe and modified Interview to the Double. Consulting with the Children's Advisory Group highlighted the importance of listening to children and recognizing and valuing children's imaginative contributions to methods for involving children in health literacy research. Insights from this commentary can be used to foreground equity-focused approaches to future research and practice with children in the field of health literacy.